Battery packaging material, battery, and method for producing battery packaging material

By adding lubricant to the hot melt resin layer of the battery packaging material and using a Vicker-shaped presser under specific conditions, the problem of battery packaging materials in the prior art being difficult to adapt to multiple shapes and sizes, and lubricant contaminates the mold, achieving efficient continuous production and diversified adaptability.

JP7662008B2Active Publication Date: 2025-04-15DAI NIPPON PRINTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023178652
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-11-30
Filing Date
2023-10-17
Publication Date
2025-04-15
Estimated Expiration
2036-11-29

AI Technical Summary

Technical Problem

When existing metal battery packaging materials face the needs of high-performance batteries such as electric vehicles and hybrid vehicles, they are difficult to adapt to the requirements of multiple shapes and thinner sizes. At the same time, their smooth surface can easily cause lubricant to contaminate the mold, affecting the continuous production efficiency of battery packaging materials.

Method used

A film-like composite material consisting of a base layer, a barrier layer and a hot melt resin layer is used, which contains a lubricant and is treated with a Vicker-shaped injector under specific temperature and humidity conditions to reduce the adhesion and transfer of the lubricant.

Benefits of technology

It effectively reduces the contamination of lubricants on the mold, improves the continuous production efficiency of battery packaging materials, and adapts to the needs of various shapes and sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662008000006
    Figure 0007662008000006
  • Figure 0007662008000007
    Figure 0007662008000007
  • Figure 0007662008000008
    Figure 0007662008000008
Patent Text Reader

Abstract

To provide a packing material for a battery with excellent continuous productivity of the battery.SOLUTION: A packing material for a battery is composed of a lamination body having at least a base material layer, a barrier layer, and a heat-seal resin layer in this order. The heat-seal resin layer contains a slip additive. At the time when the indenter in a Vickers shape is pressed at a loading speed of 5 mN / 10 sec into a front surface of a barrier layer side of the heat-seal resin layer by using PICODENTOR(R) HM500 under a temperature of 24°C and a relative humidity of 50% and a loading of the indenter reaches 3.0 mN, a pressing depth of the indenter to the heat-seal resin layer is 5.8 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material for a battery, a battery, and a method for producing a packaging material for a battery. [Background technology]

[0002] Various types of batteries have been developed, and packaging materials are essential components for sealing battery elements such as electrodes and electrolytes in all batteries. Metal packaging materials have been widely used for battery packaging in the past, but in recent years, with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., batteries are required to have a variety of shapes and are also required to be thin and lightweight. However, the metal battery packaging materials that have been widely used in the past have the disadvantages of being difficult to follow the diversification of shapes and having limited weight reduction.

[0003] In view of this, a film-like laminate in which a base material layer / adhesive layer / barrier layer / thermal adhesive resin layer are laminated in this order has been proposed as a battery packaging material that can be easily processed into various shapes and can be made thinner and lighter (see, for example, Patent Document 1). Such a film-like battery packaging material is formed so that the battery element can be sealed by heat-sealing the peripheral portions of the thermal adhesive resin layers so that they face each other.

[0004] In the battery packaging material, when the battery element is enclosed, the material is molded in a mold to form a space for accommodating the battery element. During this molding, the battery packaging material is stretched, which causes a problem that cracks and pinholes are likely to occur in the barrier layer at the flange of the mold. In order to solve this problem, a method is known in which the surface of the heat-sealable resin layer of the battery packaging material is coated with a lubricant, or a lubricant is blended into the resin forming the heat-sealable resin layer and allowed to bleed out onto the surface, thereby increasing the slipperiness of the heat-sealable resin layer. By adopting such a method, the battery packaging material is easily drawn into the mold during molding, and cracks and pinholes in the battery packaging material can be suppressed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present inventors have repeatedly studied the molding conditions of the battery packaging material, and have found that, for example, a mold for molding the battery packaging material should have a high surface smoothness (for example, a surface roughness standard piece for comparison, as specified in Table 2 of JIS B 0659-1:2002, Annex 1 (Reference) When a stainless steel mold is used, the surface Rz (maximum height roughness) is 0.8 μm or less. It was found that because the contact area between the mold and the heat-sealable resin layer becomes large, the surface of the heat-sealable resin layer is easily scraped, and the lubricant located on the surface portion of the heat-sealable resin layer is easily transferred to the mold during molding, resulting in the problem of contaminating the mold.

[0007] If another battery packaging material is molded while the mold is contaminated with the lubricant, the lubricant lumps adhering to the mold will adhere to the surface of the battery packaging material and will be used for heat-sealing the heat-sealing resin layer as is. When the heat-sealing resin layer is heat-sealed, the lubricant-adhered portion will melt unevenly, resulting in poor sealing. To prevent this, it becomes necessary to increase the frequency of cleaning to remove the lubricant adhering to the mold, which leads to a problem of reduced continuous battery productivity. A primary object of the present invention is to provide a battery packaging material that is excellent in continuous productivity of batteries, and a method for producing the same. [Means for solving the problem]

[0008] The present inventors have conducted intensive research to solve the above problems. As a result, the inventors have found that a battery packaging material consisting of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, the heat-sealable resin layer containing a lubricant, and in which, when a Vickers-shaped indenter is pressed into the surface of the heat-sealable resin layer opposite to the barrier layer at a load rate of 5 mN / 10 sec using Picodentor (registered trademark) HM500 under an environment of 24°C temperature and 50% relative humidity, the indenter has a depth of indentation of 5.8 μm or less when the load of the indenter reaches 3.0 mN, is excellent in continuous productivity of batteries because the lubricant is unlikely to adhere to the die, even when molded using, for example, a die made of stainless steel with high surface smoothness. The present invention has been completed based on these findings and through further research.

[0009] That is, the present invention provides the following aspects. Item 1. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The heat-fusible resin layer contains a lubricant, A packaging material for batteries, in which, when a Vickers-shaped indenter is pressed into the surface of the heat-sealable resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentre (registered trademark) HM500 in an environment of a temperature of 24°C and a relative humidity of 50%, the indenter has a pressing depth of 5.8 μm or less into the heat-sealable resin layer when the indenter load reaches 3.0 mN. Item 2. The battery packaging material according to Item 1, wherein the coefficient of dynamic friction of the surface of the heat-sealable resin layer opposite the barrier layer is 0.4 or less, as measured under the following test conditions: (Test conditions) The battery packaging material is placed on a horizontal surface of a rectangular metal plate with the heat-sealable resin layer facing downward. A weight of 200 g is then placed on the surface of the battery packaging material on the base layer side. The battery packaging material is then pulled 25 mm in the horizontal direction at a pulling speed of 100 mm / min, and the dynamic friction coefficient is measured. The metal plate is JIS B 0659-1:2002 Appendix 1 (Reference) Comparative surface roughness The metal plate is made of stainless steel having a surface roughness Rz (maximum height roughness) of 0.8 μm as specified in Table 2 of the thickness standard piece. The contact area between the surface of the metal plate and the heat-sealable resin layer of the battery packaging material is 160 cm 2 The weight and the base material of the battery packaging material are The surface area in contact with the layer side is 40cm 2 Let us assume that. Item 3. The battery packaging material according to Item 1 or 2, wherein the resin constituting the heat-sealable resin layer is polypropylene. Item 4. The battery packaging material according to any one of Items 1 to 3, further comprising an adhesive layer made of acid-modified polypropylene between the barrier layer and the heat-sealable resin layer. Item 5. The battery packaging material according to any one of Items 1 to 4, wherein the barrier layer is made of an aluminum alloy or stainless steel. Item 6. The battery packaging material according to any one of Items 1 to 5, further comprising an acid-resistant coating layer on at least one surface of the barrier layer. Item 7. The packaging material for a battery according to any one of Items 1 to 6, which is a packaging material for a secondary battery. Item 8. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a packaging body formed from the battery packaging material according to any one of Items 1 to 7. Item 9. The method includes a step of laminating at least a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, The heat-sealable resin layer contains a lubricant, In the above process, a Vickers-shaped indenter is pressed into the surface of the thermally adhesive resin layer on the barrier layer side at a loading rate of 5 mN / 10 sec using a Picodentre (registered trademark) HM500 in an environment of a temperature of 24°C and a relative humidity of 50%, and a thermally adhesive resin layer is laminated such that the indenter has a pressing depth of 5.8 μm or less into the thermally adhesive resin layer when the indenter load reaches 3.0 mN. Effect of the Invention

[0010] According to the present invention, it is possible to provide a battery packaging material that is excellent in continuous productivity of batteries, and a method for producing the same. [Brief description of the drawings]

[0011] [Figure 1] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 2] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 3] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Figure 4] FIG. 2 is a schematic diagram for explaining the operation of pressing an indenter into the surface of a heat-sealable resin layer of the battery packaging material of the present invention. [Diagram 5] FIG. 2 is a schematic diagram for explaining a method for measuring the dynamic friction coefficient of the surface of the heat-sealable resin layer of the battery packaging material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The battery packaging material of the present invention is characterized in that it comprises a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, the heat-sealable resin layer contains a lubricant, and when a Vickers-shaped indenter is pressed into the surface of the heat-sealable resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentor (registered trademark) HM500 in an environment of 24°C temperature and 50% relative humidity, the indenter has a pressing depth of 5.8 μm or less into the heat-sealable resin layer when the indenter load reaches 3.0 mN. The battery packaging material of the present invention and its manufacturing method will be described in detail below.

[0013] In this specification, the numerical range indicated by "to" means "greater than or equal to" or "less than or equal to." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0014] 1.Laminated structure of battery packaging material 1, the battery packaging material 10 is composed of a laminate in which at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order. In the battery packaging material of the present invention, the base material layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. That is, when the battery is assembled, the heat-sealable resin layers 4 located on the periphery of the battery element are thermally welded together to seal the battery element, thereby sealing the battery element.

[0015] As shown in Fig. 2, the battery packaging material 10 of the present invention may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of enhancing adhesion therebetween. Also, as shown in Fig. 3, an adhesive layer 5 may be provided between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, for the purpose of enhancing adhesion therebetween.

[0016] 2. Composition of each layer forming the battery packaging material [Base material layer 1] In the battery packaging material of the present invention, the base layer 1 is a layer located on the outermost layer side. The material forming the base layer 1 is not particularly limited as long as it has insulating properties. Examples of materials forming the base layer 1 include polyester, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures and copolymers thereof.

[0017] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, polycarbonate, copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit, copolymerized polyesters mainly composed of butylene terephthalate as a repeating unit, etc. Specific examples of copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit include copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit and ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. Specific examples of copolymer polyesters containing butylene terephthalate as the main repeating unit include copolymer polyesters in which butylene terephthalate as the main repeating unit is polymerized with butylene isophthalate (hereinafter abbreviated as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more. Polyesters have the advantage of being excellent in electrolyte resistance and being less likely to cause whitening or the like due to adhesion of electrolyte, and are therefore suitably used as materials for forming the base layer 1.

[0018] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid; aromatic polyamides such as polymetaxylylene adipamide (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); and polyamides containing lactam components and isocyanate components such as 4,4'-diphenylmethane diisocyanate. Examples of the polyamide include a polyesteramide copolymer and a polyetheresteramide copolymer, which are copolymers of a copolymerized polyamide with a polyester or a polyalkylene ether glycol; and copolymers thereof. These polyamides may be used alone or in combination of two or more. Stretched polyamide films have excellent stretchability and can prevent whitening due to resin cracking of the base layer 1 during molding, and are therefore preferably used as a material for forming the base layer 1.

[0019] The substrate layer 1 may be formed of a uniaxially or biaxially stretched resin film, or may be formed of an unstretched resin film. Among them, a uniaxially or biaxially stretched resin film, particularly a biaxially stretched resin film, is preferably used as the substrate layer 1 because its heat resistance is improved by oriented crystallization. The substrate layer 1 may be formed by coating the barrier layer 3 with the above-mentioned material.

[0020] Among these, the resin film forming the base layer 1 is preferably nylon or polyester, more preferably biaxially oriented nylon or biaxially oriented polyester, and particularly preferably biaxially oriented nylon.

[0021] In order to improve pinhole resistance and insulation when used as a battery packaging body, the base layer 1 can be laminated with at least one of resin films and coatings made of different materials. Specifically, a multi-layer structure in which a polyester film and a nylon film are laminated, a multi-layer structure in which a biaxially oriented polyester and a biaxially oriented nylon are laminated, and the like can be mentioned. When the base layer 1 is made into a multi-layer structure, each resin film may be bonded via an adhesive, or may be directly laminated without an adhesive. When bonding without an adhesive, for example, a method of bonding in a thermally molten state such as a co-extrusion lamination method, a sandwich lamination method, a thermal lamination method, and the like can be mentioned. In addition, when bonding via an adhesive, the adhesive used may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a heat pressure type, an electron beam curing type, an ultraviolet curing type, and the like. Examples of adhesive components include polyester-based resins, polyether-based resins, polyurethane-based resins, epoxy-based resins, phenolic resins, polyamide-based resins, polyolefin-based resins, polyvinyl acetate-based resins, cellulose-based resins, (meth)acrylic resins, polyimide-based resins, amino resins, rubber, and silicone-based resins.

[0022] The thickness of the base layer 1 is, for example, about 4 to 50 μm, and preferably about 9 to 30 μm.

[0023] [Adhesive layer 2] In the battery packaging material of the present invention, the adhesive layer 2 is a layer that is provided as needed to bond the base material layer 1 and the barrier layer 3 together.

[0024] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive used to form the adhesive layer 2 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0025] Specific examples of the resin component of the adhesive that can be used to form the adhesive layer 2 include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, polycarbonate, and copolymerized polyester; polyether-based adhesives; polyurethane-based adhesives; epoxy-based resins; phenolic resin-based resins; polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymerized polyamide; polyolefin-based resins such as polyolefin, acid-modified polyolefin, and metal-modified polyolefin; polyvinyl acetate-based resins; cellulose-based adhesives; (meth)acrylic resins; polyimide-based resins; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone-based resins; and fluorinated ethylene propylene copolymers. These adhesive components may be used alone or in combination of two or more. The combination of two or more adhesive components is not particularly limited, and examples of the adhesive components include a mixed resin of polyamide and acid-modified polyolefin, a mixed resin of polyamide and metal-modified polyolefin, a mixed resin of polyamide and polyester, a mixed resin of polyester and acid-modified polyolefin, a mixed resin of polyester and metal-modified polyolefin, etc. Among these, from the viewpoints of excellent spreadability, durability and yellowing inhibition effect under high humidity conditions, and heat deterioration inhibition effect during heat sealing, and of effectively suppressing the occurrence of delamination by suppressing the decrease in laminate strength between the base layer 1 and the barrier layer 3, preferred are polyurethane-based two-component curing adhesives; polyamide, polyester, or a blend resin of these with modified polyolefin.

[0026] The adhesive layer 2 may be multi-layered with different adhesive components. When the adhesive layer 2 is multi-layered with different adhesive components, from the viewpoint of improving the laminate strength between the base material layer 1 and the barrier layer 3, it is preferable to select a resin having excellent adhesion to the base material layer 1 as the adhesive component arranged on the base material layer 1 side, and an adhesive component having excellent adhesion to the barrier layer 3 as the adhesive component arranged on the barrier layer 3 side. When the adhesive layer 2 is multi-layered with different adhesive components, specifically, preferred examples of the adhesive component arranged on the barrier layer 3 side include acid-modified polyolefin, metal-modified polyolefin, a mixed resin of polyester and acid-modified polyolefin, and a resin containing copolymerized polyester.

[0027] The thickness of the adhesive layer 2 is, for example, about 2 to 50 μm, and preferably about 3 to 25 μm.

[0028] [Barrier layer 3] In the battery packaging material, the barrier layer 3 is a layer that has the function of preventing water vapor, oxygen, light, and the like from penetrating into the inside of the battery in addition to improving the strength of the battery packaging material. Specific examples of metals constituting the barrier layer 3 include aluminum, stainless steel, and titanium, and preferably aluminum. The barrier layer 3 can be formed, for example, of a metal foil, a metal vapor deposition film, an inorganic oxide vapor deposition film, a carbon-containing inorganic oxide vapor deposition film, or a film provided with these vapor deposition films, and is preferably formed of a metal foil, and more preferably formed of an aluminum alloy foil. From the viewpoint of preventing wrinkles and pinholes from occurring in the barrier layer 3 during the production of the battery packaging material, the barrier layer is more preferably formed of a soft aluminum alloy foil such as annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0029] The thickness of the barrier layer 3 is, for example, about 10 to 200 μm, and preferably about 20 to 100 μm.

[0030] In addition, in order to stabilize adhesion and prevent dissolution and corrosion, it is preferable that at least one surface of the barrier layer 3, preferably at least the surface on the thermal adhesive resin layer 4 side, and more preferably both surfaces are chemically treated. Here, the chemical conversion treatment is a treatment for forming an acid-resistant film on the surface of the barrier layer 3. That is, it is preferable that the barrier layer 3 has an acid-resistant film layer on at least one surface thereof. Examples of chemical conversion treatments for forming an acid-resistant film layer include chromate treatment using a chromate compound such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate; phosphate treatment using a phosphate compound such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and chromate treatment using an aminated phenol polymer consisting of repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.

[0031] [ka]

[0032] [ka]

[0033] [ka]

[0034] [ka]

[0035] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1and R 2 In the general formulae (1) to (4), X and R are the same or different and each represents a hydroxyl group, an alkyl group, or a hydroxyalkyl group. 1 , R 2 Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 , R 2 Examples of the hydroxyalkyl group represented by the formula (1) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as hydroxymethyl, 1-hydroxyethyl, 2-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 3-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 3-hydroxybutyl, and 4-hydroxybutyl. In the formulas (1) to (4), X is preferably any one of a hydrogen atom, a hydroxyl group, and a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer composed of the repeating units represented by the formulas (1) to (4) is, for example, about 500 to about 1,000,000, and preferably about 1,000 to about 20,000.

[0036] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is available in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form an acid-resistant coating layer on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be formed on the acid-resistant coating layer. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is grafted to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, a silane coupling agent, and the like. These crosslinking agents may be used alone or in combination of two or more.

[0037] These chemical conversion treatments may be performed using one type of chemical conversion treatment alone, or two or more types of chemical conversion treatments in combination. Furthermore, these chemical conversion treatments may be performed using one type of compound alone, or two or more types of compounds in combination. Among these, preferred is a chromate treatment with chromate acid, and more preferred is a chromate treatment using a combination of a chromate compound, a phosphoric acid compound, and an aminated phenol polymer.

[0038] The amount of the acid-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, when a chromate treatment is performed using a combination of a chromic acid compound, a phosphoric acid compound, and an aminated phenol polymer, the amount of the acid-resistant film formed on the surface of the barrier layer 3 is about 1 μm. 2 Hit, Chrome It is desirable that the acid compound is contained in an amount of about 0.5 to about 50 mg, preferably about 1.0 to about 40 mg, calculated as chromium, the phosphorus compound is contained in an amount of about 0.5 to about 50 mg, preferably about 1.0 to about 40 mg, calculated as phosphorus, and the aminated phenol polymer is contained in an amount of about 1 to about 200 mg, preferably about 5.0 to 150 mg.

[0039] The chemical conversion treatment is carried out by applying a solution containing a compound used to form an acid-resistant film to the surface of the barrier layer 3 by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer 3 so that the temperature of the barrier layer 3 is about 70 to 200° C. Furthermore, before the chemical conversion treatment is carried out on the barrier layer 3, the barrier layer 3 may be previously subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, the chemical conversion treatment of the surface of the barrier layer 3 can be carried out more efficiently.

[0040] [Thermal adhesive resin layer 4] In the battery packaging material of the present invention, the heat-sealable resin layer 4 corresponds to the innermost layer, and is a layer that seals the battery element by being heat-sealed to each other when the battery is assembled.

[0041] In the present invention, the heat-fusible resin layer contains a lubricant. The lubricant is not particularly limited, but preferably includes an amide-based lubricant. The amide-based lubricant is not particularly limited as long as it has an amide group, but preferably includes fatty acid amide and aromatic bisamide. The lubricant may be used alone or in combination of two or more kinds.

[0042] Examples of fatty acid amides include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, and unsaturated fatty acid bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, and N,N'-cystearylisophthalic acid amide.

[0043] The content of the lubricant in the heat-sealable resin layer 4 is not particularly limited, but from the viewpoint of improving the moldability of the battery packaging material while suppressing adhesion of the lubricant to the mold during molding and achieving excellent continuous productivity of the battery, the content is preferably about 100 to 2000 ppm, and more preferably about 500 to 1200 ppm.

[0044] The heat-sealable resin layer 4 is preferably formed of polyolefin. The polyolefin is not particularly limited as long as it is heat-sealable, and examples thereof include polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin.

[0045] Specific examples of the polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); ethylene-butene-propylene terpolymers; etc. Among these polyolefins, polyethylene and polypropylene are preferable.

[0046] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these polyolefins, preferred are cyclic alkenes, and more preferred are norbornene.

[0047] The carboxylic acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0048] The carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride to the cyclic polyolefin. The cyclic polyolefin to be modified with the carboxylic acid is the same as described above. The carboxylic acid used for the modification is the same as that used for the modification of the acid-modified cycloolefin copolymer.

[0049] Among these resin components, polypropylene is preferred as the resin constituting the heat-sealable resin layer 4, and random polypropylene is more preferred. That is, the heat-sealable resin layer 4 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The fact that the heat-sealable resin layer 4 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography mass spectrometry, and the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, peaks derived from maleic anhydride are detected at wave numbers around 1760 cm-1 and 1780 cm-1. However, if the degree of acid modification is low, the peaks may become small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy. As the resin constituting the surface of the heat-sealable resin layer 4 into which the indenter is pressed, polypropylene is preferred, and random polypropylene is more preferred.

[0050] The thermally adhesive resin layer 4 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0051] In the present invention, the heat-sealable resin layer 4 is characterized in that, using a Picodentre (registered trademark) HM500 in an environment of a temperature of 24°C and a relative humidity of 50%, as shown in Figure 4, a Vickers-shaped indenter P is pressed against the surface 4a of the heat-sealable resin layer 4 opposite the barrier layer 3 at a loading speed of 5 mN / 10 sec (pressed in the thickness direction of the heat-sealable resin layer 4), and the indenter has a pressing depth of 5.8 μm or less when the indenter load reaches 3.0 mN.

[0052] As mentioned above, when a stainless steel die with high surface smoothness (for example, a die with a surface Rz (maximum height roughness) of 0.8 μm as specified in Table 2 of the comparative surface roughness standard pieces in JIS B 0659-1:2002, Annex 1 (reference), for reference. Note that a comparative surface roughness standard piece manufactured by Nippon Kinzoku Denchu ​​is used to confirm Rz) is used as a die for forming the battery packaging material, the contact area between the die and the heat-sealable resin layer becomes large, so that the lubricant located on the surface of the heat-sealable resin layer is easily scraped off and the lubricant located on the surface portion of the heat-sealable resin layer is easily transferred to the die, contaminating the die and causing a problem of reduced continuous productivity of batteries.

[0053] In contrast, in the battery packaging material of the present invention, since the heat-sealable resin layer 4 has the above-mentioned specific hardness, even when the material is molded using a mold with high surface smoothness, the lubricant located on the surface of the heat-sealable resin layer is not easily scraped off, and the lubricant located on the surface portion of the heat-sealable resin layer is not easily transferred to the mold, and contamination of the mold is effectively suppressed. Therefore, by using the battery packaging material of the present invention in the production of batteries, the continuous productivity of batteries can be improved.

[0054] From the viewpoint of further increasing the continuous productivity of the battery, the pressing depth of the pressing pin into the heat-sealable resin layer 4 is preferably about 5.5 μm or less, more preferably about 5.3 μm or less. From the viewpoint of ease of comparing and determining the pressing amount, the lower limit of the pressing depth is, for example, about 4.5 μm or about 4.8 μm.

[0055] The Vickers-shaped indenter used in the present invention is an indenter (Vickers type) having a diamond tip with a regular square pyramid tip shape.

[0056] Furthermore, in the battery packaging material of the present invention, the dynamic friction coefficient of the surface 4a of the heat-sealable resin layer 4 opposite the barrier layer 3, measured under the following test conditions (based on JIS K7125:1999), is preferably 0.4 or less. This allows the moldability and continuous productivity of the battery using the battery packaging material of the present invention to be further improved. The dynamic friction coefficient is measured in an environment of a temperature of 24°C and a relative humidity of 50%.

[0057] (Test conditions) As shown in Fig. 5, the battery packaging material 10 is placed on the surface of a metal plate 11 that is rectangular in plan view and placed on a horizontal surface 20, with the heat-sealable resin layer 4 facing downward. Next, a weight 12 weighing 200 g is placed on the surface of the base material layer 1 side of the battery packaging material 10. Next, the battery packaging material 10 is pulled 25 mm in the horizontal direction (perpendicular to the thickness direction of the heat-sealable resin layer 4) at a pulling speed of 100 mm / min, and the dynamic friction coefficient at this time is measured. The metal plate 11, battery packaging material 10, and weight 12 are placed so that their centers coincide when viewed in plan in a stacked state. The metal plate 11 is made of stainless steel with a surface Rz (maximum height roughness) of 0.8 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002, Appendix 1 (reference). The contact area between the surface of the metal plate 11 and the heat-sealable resin layer 4 of the battery packaging material 10 is 160 cm. 2 (The contact surface is a square.) The contact area between the weight 12 and the surface of the battery packaging material 10 on the base layer 1 side is 40 cm 2 (The contacting surface is a square.)

[0058] From the viewpoint of ease of comparison and judgment of the amount of pushing, the lower limit of the dynamic friction coefficient may be, for example, 0.1 or even 0.2.

[0059] In the present invention, the above-mentioned indentation depth can be adjusted, for example, by adjusting the melt mass flow rate (MFR) of the resin constituting the heat-fusible resin layer 4. The MFR of the resin constituting the heat-fusible resin layer 4 at 230°C is preferably 5.0 g / 10 min or more, more preferably about 10 to 20 g / 10 min. The higher the MFR, the deeper the indentation depth tends to be, and the lower the MFR, the shallower the indentation depth tends to be. Note that a commercially available product can be used as the resin having the desired MFR.

[0060] The thickness of the heat-fusible resin layer 4 can be appropriately selected, and is, for example, about 10 to 100 μm, and preferably about 15 to 50 μm.

[0061] [Adhesive layer 5] In the battery packaging material of the present invention, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 and the heat-sealable resin layer 4 in order to firmly bond them together.

[0062] The adhesive layer 5 is formed by an adhesive capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The adhesive mechanism, the type of adhesive component, etc. of the adhesive used to form the adhesive layer 5 can be the same as those of the adhesive layer 2. The adhesive layer 5 can also be composed of the resin exemplified in the heat-sealable resin layer 4. When the resin exemplified in the heat-sealable resin layer 4 is used as the adhesive component used in the adhesive layer 5, the adhesive component can be an acid-modified polyolefin, preferably a carboxylic acid-modified polyolefin, and particularly preferably a carboxylic acid-modified polypropylene. Specific examples of these resins can be the same as those of the heat-sealable resin layer 4. In particular, carboxylic acid-modified polypropylene is preferable because it has excellent adhesion to the barrier layer. That is, the adhesive layer 5 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The adhesive layer 5 can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, peaks derived from maleic anhydride are detected at wave numbers of around 1760 cm-1 and 1780 cm-1. However, if the degree of acid modification is low, the peaks are small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.

[0063] The thickness of the adhesive layer 5 is, for example, about 2 to 50 μm, and preferably about 15 to 40 μm.

[0064] 3. Manufacturing method of battery packaging material The method for producing the battery packaging material of the present invention is not particularly limited as long as a laminate in which each layer of a predetermined composition is laminated can be obtained. That is, the battery packaging material of the present invention includes a step of obtaining a laminate by laminating at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, and the heat-sealable resin layer contains a lubricant, and in the step, a Vickers-shaped indenter is pressed against the surface of the heat-sealable resin layer opposite to the barrier layer at a loading speed of 5 mN / 10 sec using Picodentor (registered trademark) HM500 under an environment of 24°C and 50% relative humidity, and the heat-sealable resin layer can be produced by laminating the heat-sealable resin layer such that the indenter's indentation depth into the heat-sealable resin layer at the time when the indenter's load reaches 3.0 mN is 5.8 μm or less.

[0065] The composition of each layer of the battery packaging material is as described above. Specific examples of the method for producing the battery packaging material of the present invention include the following methods.

[0066] First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which the base layer 1, adhesive layer 2, and barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used to form the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as extrusion, gravure coating, or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.

[0067] Next, the heat-sealable resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-sealable resin layer 4 is directly laminated on the barrier layer 3, the resin components constituting the heat-sealable resin layer 4 may be applied on the barrier layer 3 of the laminate A by a method such as gravure coating or roll coating. When an adhesive layer 5 is provided between the barrier layer 3 and the heat-sealable resin layer 4, for example, (1) the adhesive layer 5 and the heat-sealable resin layer 4 may be co-extruded on the barrier layer 3 of the laminate A. (2) a method in which an adhesive layer 5 and a heat-sealable resin layer 4 are laminated separately (co-extrusion lamination method); (3) forming a laminate in which the barrier layer 3 and the adhesive layer 5 are formed by extruding an adhesive onto the barrier layer 3 of the laminate A by a thermal lamination method; (4) a method of laminating the barrier layer 3 of the laminate A and the heat-sealable resin layer 4 formed in advance into a sheet shape by a thermal lamination method on the adhesive layer 5; and a method (sandwich lamination method) in which the laminate A and the heat-fusible resin layer 4 are bonded together via the adhesive layer 5 while pouring the molten adhesive layer 5 between the adhesive layer 2 and the adhesive layer 5 that is provided as needed. In order to strengthen the adhesiveness of the adhesive layer 2 and the adhesive layer 5 that is provided as needed, the laminate A and the heat-fusible resin layer 4 may be subjected to a heat treatment such as a hot roll contact type, hot air type, near or far infrared type. Conditions for such a heat treatment include, for example, 150 to 250°C for 1 to 5 minutes.

[0068] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, in order to improve or stabilize the film-forming properties, lamination processing, suitability for secondary processing of the final product (pouching, embossing), etc.

[0069] 4. Applications of battery packaging materials The battery packaging material of the present invention is used as a packaging material for hermetically housing battery elements such as a positive electrode, a negative electrode, and an electrolyte.

[0070] Specifically, a battery element including at least a positive electrode, a negative electrode, and an electrolyte is covered with the battery packaging material of the present invention in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the battery element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide a battery using the battery packaging material. When the battery packaging material of the present invention is used to house a battery element, the sealant portion of the battery packaging material of the present invention is used so as to face inside (the surface in contact with the battery element).

[0071] The battery packaging material of the present invention may be used for either primary or secondary batteries, but is preferably used for secondary batteries. The type of secondary battery to which the battery packaging material of the present invention is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries are suitable applications of the battery packaging material of the present invention. EXAMPLES

[0072] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0073] Examples 1 to 12 and Comparative Examples 1 to 2 <Production of battery packaging materials> A barrier layer (40 μm thick) shown in Table 1, which had been subjected to chemical conversion treatment on both sides, was laminated on the substrate layer shown in Table 1 by dry lamination. Specifically, a two-liquid urethane adhesive (a polyol compound and an aromatic isocyanate compound) was applied to one side of the barrier layer, and an adhesive layer (3 μm thick) was formed on the barrier layer. When the substrate layer was a single layer, the thickness was 25 μm, and the PET / nylon was laminated in the order of PET (12 μm) and nylon (15 μm) from the outer side (the opposite side to the barrier layer) of the battery packaging material. Next, the adhesive layer on the barrier layer and the substrate layer were laminated by dry lamination, and then aging treatment was performed at 40° C. for 24 hours to produce a substrate layer / adhesive layer / barrier layer laminate. The chemical conversion treatment of the barrier layer was performed by using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) by roll coating. The adhesive was applied to both sides of the laminate and baked. Next, 40 μm of acid-modified polypropylene (PPa, placed on the barrier layer side) and 40 μm of polypropylene (PP, on the innermost layer side) were co-extruded on the barrier layer of the laminate, thereby laminating an adhesive layer and a heat-sealable resin layer on the barrier layer, thereby obtaining a battery packaging material in which the base layer / adhesive layer / barrier layer / adhesive layer / heat-sealable resin layer were laminated in this order. Details of the acid-modified polyolefin and polypropylene used in the examples and comparative examples are as follows (Table 1).

[0074] Acid-modified polypropylene A (PPa-A): Maleic anhydride-modified polypropylene with MFR of 8g / 10min at 230℃ and lubricant content of 0ppm Acid-modified polypropylene B (PPa-B): Maleic anhydride-modified polypropylene with MFR of 10 g / 10 min at 230°C and lubricant content of 0 ppm Acid-modified polypropylene C (PPa-C): Maleic anhydride-modified polypropylene with MFR of 12 g / 10 min at 230°C and 0 ppm lubricant content Polypropylene A (PP-A): Random polypropylene with MFR of 16 g / 10 min at 230°C and containing 700 ppm of erucic acid amide as a lubricant. Polypropylene B (PP-B): Random polypropylene with MFR of 20 g / 10 min at 230°C and containing 700 ppm of erucic acid amide as a lubricant. Polypropylene C (PP-C): Random polypropylene with MFR of 20 g / 10 min at 230°C and containing 1200 ppm of erucic acid amide as a lubricant. Polypropylene D (PP-D): Random polypropylene with MFR of 18 g / 10 min at 230°C and containing 1200 ppm of erucic acid amide as a lubricant.

[0075] <Measurement of indentation depth using Picodentor> Using a pico-denter (Fisher Instruments HM-500), the indentation depth of the surface of the heat-sealable resin layer of each battery packaging material obtained above was measured. Specifically, using a pico-denter, in an environment of 24°C temperature and 50% relative humidity, the indenter was gradually pressed into the surface of the barrier layer side of the heat-sealable resin layer at a loading speed of 5mN / 10sec, and the indentation depth of the indenter was measured when the load of the indenter reached 3.0mN. The results are shown in Table 1. The indenter used was a square pyramid (Vickers type, facing angle 136°) with a diamond tip.

[0076] <Measurement of dynamic friction coefficient> The dynamic friction coefficient of the surface of the heat-sealable resin layer of each of the battery packaging materials obtained above was measured under the following test conditions. The results are shown in Table 1. (Test conditions) The battery packaging material is placed on the surface of a rectangular metal plate placed on a horizontal surface, with the heat-sealable resin layer facing downward. A weight of 200 g is then placed on the surface of the base material layer side of the battery packaging material. The battery packaging material is then pulled 25 mm in the horizontal direction at a pulling speed of 100 mm / min, and the dynamic friction coefficient at this time is measured. The metal plate is made of stainless steel with a surface Rz (maximum height roughness) of 0.8 μm as specified in Table 2 of the comparative surface roughness standard piece in JIS B 0659-1:2002, Appendix 1 (Reference). The contact area between the surface of the metal plate and the heat-sealable resin layer of the battery packaging material is 160 cm2.2 (The contact surface is square.) The contact area between the weight and the surface of the battery packaging material on the base layer side is 40 cm 2 (The contacting surface is a square.)

[0077] (Evaluation of continuous battery productivity) Each battery packaging material obtained above was cut into a square of 80 mm x 120 mm to prepare samples. Next, in an environment of 24°C and 50% relative humidity, these samples were cold-formed, 500 pieces each, at a pressure of 0.4 MPa and a depth of 5 mm, using a molding die (female die) with an aperture of 30 x 50 mm and a corresponding molding die (male die). Next, the corners of the die after cold forming were visually observed, and when the lubricant was transferred to the die and whitened, it was evaluated as low continuous productivity (C), and when there was no whitening, it was evaluated as high continuous productivity (A). The results are shown in Table 1. The male and female dies were, respectively, those specified in Table 2 of the comparative surface roughness standard pieces in JIS B 0659-1:2002, Appendix 1 (Reference), A stainless steel mold with a maximum height roughness (Rz) of 0.8 μm was used.

[0078] [Table 1]

[0079] The notes for Table 1 are as follows: Ny: Nylon PET: Polyethylene terephthalate PBT: Polybutylene terephthalate PP: Polypropylene PPa: Acid-modified polypropylene PET / nylon is a battery packaging material in which PET (12 μm) and nylon (15 μm) are layered from the outside (the side opposite the barrier layer). AL: Aluminum alloy SUS: Stainless steel

[0080] As is clear from the results shown in Table 1, the battery packaging materials of Examples 1 to 12, in which the indentation depth on the surface of the heat-sealable resin layer is 5.5 μm or less, are excellent in continuous battery productivity. On the other hand, the battery packaging materials of Comparative Examples 1 and 2, in which the indentation depth on the surface of the heat-sealable resin layer is 6.2 μm or 6.1 μm, are inferior in continuous battery productivity. [Explanation of symbols]

[0081] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 4a: Barrier layer side surface of heat-sealable resin layer 5 Adhesive layer 10 Packaging materials for batteries 11 Metal plate 12 Weight 20 horizontal plane P Vickers shape indenter

Claims

1. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The substrate layer comprises polyester and polyamide, the barrier layer comprises aluminum; The heat-fusible resin layer contains a lubricant, a Vickers-shaped indenter is pressed into the surface of the thermally adhesive resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentor (registered trademark) HM500 under an environment of a temperature of 24° C. and a relative humidity of 50%, and the indenter has a depth of indentation of 5.8 μm or less into the thermally adhesive resin layer when the load of the indenter reaches 3.0 mN; A packaging material for batteries, wherein the resin constituting the surface of the heat-sealable resin layer against which the indenter is pressed is polypropylene.

2. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The base layer comprises polyester, the barrier layer comprises aluminum; The heat-fusible resin layer contains a lubricant, a Vickers-shaped indenter is pressed into the surface of the thermally adhesive resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentor (registered trademark) HM500 under an environment of a temperature of 24° C. and a relative humidity of 50%, and the indenter has a depth of indentation of 5.8 μm or less into the thermally adhesive resin layer when the load of the indenter reaches 3.0 mN; A packaging material for batteries, wherein the resin constituting the surface of the heat-sealable resin layer against which the indenter is pressed is polypropylene.

3. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The base layer comprises polyester, The barrier layer includes stainless steel, The heat-fusible resin layer contains a lubricant, a Vickers-shaped indenter is pressed into the surface of the thermally adhesive resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentor (registered trademark) HM500 under an environment of a temperature of 24° C. and a relative humidity of 50%, and the indenter has a depth of indentation of 5.8 μm or less into the thermally adhesive resin layer when the load of the indenter reaches 3.0 mN; A packaging material for batteries, wherein the resin constituting the surface of the heat-sealable resin layer against which the indenter is pressed is polypropylene.

4. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The base layer is formed of an unstretched resin film, the barrier layer comprises aluminum; The heat-fusible resin layer contains a lubricant, a Vickers-shaped indenter is pressed into the surface of the thermally adhesive resin layer opposite the barrier layer at a load rate of 5 mN / 10 sec using a Picodentor (registered trademark) HM500 under an environment of a temperature of 24° C. and a relative humidity of 50%, and the indenter has a depth of indentation of 5.8 μm or less into the thermally adhesive resin layer when the load of the indenter reaches 3.0 mN; A packaging material for batteries, wherein the resin constituting the surface of the heat-sealable resin layer against which the indenter is pressed is polypropylene.

5. The battery packaging material according to any one of claims 1 to 4, wherein the barrier layer has a thickness of 100 µm or less and 40 µm or less, or more than 40 µm and 100 µm or less.

6. The battery packaging material according to any one of claims 1 to 5, wherein the thickness of the base material layer is 50 µm or less and 30 µm or less, or more than 30 µm and 50 µm or less.

7. The battery packaging material according to any one of claims 1 to 6, wherein the thickness of the heat-sealable resin layer is 100 µm or less, 15 µm or more and 50 µm or less, or more than 50 µm and 100 µm or less.

8. The battery packaging material according to any one of claims 1 to 7, wherein the heat-sealable resin layer is formed of two or more layers made of the same or different resin components.

9. The battery packaging material according to any one of claims 1 to 8, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer.

10. The battery packaging material according to claim 9 , wherein the adhesive layer has a thickness of 15 μm or more and 40 μm or less.

11. The battery packaging material according to any one of claims 1 to 10, wherein a dynamic friction coefficient of a surface of the heat-sealable resin layer opposite to the barrier layer, measured under the following test conditions, is 0.4 or less. (Test conditions) The battery packaging material is placed on a horizontal surface of a rectangular metal plate with the heat-sealable resin layer facing downward. A weight of 200 g is then placed on the surface of the battery packaging material on the base layer side. The battery packaging material is then pulled 25 mm in the horizontal direction at a pulling speed of 100 mm / min, and the dynamic friction coefficient at this time is measured. The metal plate is made of stainless steel having a surface Rz (maximum height roughness) of 0.8 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002, Appendix 1 (Reference). The contact area between the surface of the metal plate and the heat-sealable resin layer of the battery packaging material is 160 cm2. 2 The contact area between the weight and the surface of the battery packaging material on the base layer side is 40 cm 2 Let us assume that.

12. A battery comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a pouch formed from the battery packaging material according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Laminated material for secondary cell case and secondary cell case

    JP2003288866A

  • Laminate for battery pack

    JP2006147551A

  • Layered package material, outer package material for battery, and the battery

    JP2008287971A

  • External facing material for secondary battery and secondary battery

    JP2013101764A

  • Battery-packaging material

    JP2015185277A